Eklampsia dengan Partial HELLP Syndrome pada Kehamilan Usia Maternal Lanjut dengan Antenatal Care Minimal: Laporan Kasus dari Jakarta - Resya Pricilia; Widodo A; Dara Sjahruddin D (Lembaga Pengembangan Kinerja Dosen, 2026)
Eclampsia with partial HELLP syndrome in high-risk pregnancies can progress rapidly when early detection through antenatal care is inadequate. We report a 41-year-old G2P1A0 woman who presented at 37 weeks with tonic–clonic seizures, severe hypertension, proteinuria, elevated liver enzymes, and borderline thrombocytopenia, having attended only one antenatal visit at 25 weeks, resulting in missed opportunities for preeclampsia risk screening and aspirin–calcium prophylaxis. Emergency management followed ABCDE stabilization, magnesium sulfate therapy, rapid-acting antihypertensives, intravenous access, NG tube insertion, urinary catheterization, and subsequent emergency cesarean section with Pomeroy tubectomy, yielding a 2690-gram neonate with good adaptation. Despite the severe presentation, timely and guideline-based emergency actions led to favorable maternal and neonatal outcomes. This case highlights the importance of adequate antenatal screening, early recognition of hypertensive disorders, and the need to strengthen preventive strategies in primary care to avoid similar occurrences.